Mechanisms, diagnosis, prevention and management of perioperative opioid-induced hyperalgesia - Wilson, Sylvia H (Pain Manag, 2021)
Opioid-induced hyperalgesia (OIH) occurs when opioids paradoxically enhance the pain they are prescribed to ameliorate. To address a lack of perioperative awareness, we present an educational review of clinically relevant aspects of the disorder. Although the mechanisms of OIH are thought to primarily involve medullary descending pathways, it is likely multifactorial with several relevant therapeutic targets. We provide a suggested clinical definition and directions for clinical differentiation of OIH from other diagnoses, as this may be confusing but is germane to appropriate management. Finally, we discuss prevention including patient education and analgesic management choices. As prevention may serve as the best treatment, patient risk factors, opioid mitigation, and both pharmacologic and non-pharmacologic strategies are discussed.